DEKONSTRUKSI PENGAWASAN PERATURAN DAERAH SETELAH BERLAKUNYA UNDANG-UNDANG NOMOR 11 TAHUN 2020 TENTANG CIPTA KERJA - Basri Mulyani (JURIDICA : Jurnal Fakultas Hukum Universitas Gunung Rinjani, 2020)
Constitutional Court Decision of Number 137/PUU-XIII/2015and Decision Number 56/PUU-XIV/2016 which state that theauthority of the Minister of Home Affairs and the Governor asthe representative of the central government in cancelingProvincial Regulations, District Regulation/City Regulation,Governor Regulation, and Regent Regulation/Regulation ofMayor was inconstitutional. So only the Supreme Court has theauthority to revoke Provincial Regulations, DistrictRegulation/City Regulations, Governor Regulation, and RegentRegulation/Regulation of Mayor. This analysis makes use of thelegal juridical normative research method. The results showthat in a state of unity it is appropriate that higher levels ofgovernment are given the authority to supervise theregulations set in the regions. The supervision can beimplemented by conducting such a guidance to the regionthrough the strengthening of executive preview or legal normreview before it is legally binding in general